Making the best even better: fine-tuning development and learning to achieve international success in cross-country skiing - Hansen, P. Oe. (2014)
The aim of this study is to systematically analyse the leadership and management of Norwegian elite cross-country skiing. More specifically, the thesis investigates how patterns of interaction within the context of Norwegian elite cross-country skiing shape athletes` reflection on training. Engaging in reflection is considered important to learn reliably from experience to improve the quality of everyday training and development. Consequently, quality of training increases the possibility for continuous development and hence sustained success in elite sports. The main research question is: How do the national elite teams in Norwegian crosscountry skiing fine-tune processes of training and development?